Statistics as an Instrument of Ideological Confrontation - L. A. Davletshina; M. V. Karmanov (Статистика и экономика, 2023)
The relevance of the study lies in the fact that only with a competent comprehensive assessment of quantitative parameters, their qualitative interpretation is possible. Statistics acts as such a tool.The purpose of the study. The purpose of this paper is to study opinions and approaches in the use of statistics as a tool for assessing phenomena and processes.Materials and methods. In the course of the study, the main directions of statistics as a tool for working with data were studied. The most common and practically justified is the use of statistics as a tool of cognition, management, propaganda and control. The result of the interpretation of statistical data primarily depends on the degree of objectivity and the level of literacy of those who work with the data: both at the initial stage of the formation of the initial data set, and at the stage of explaining the resulting values.Results. It is revealed that the same parameters (proportions) can be interpreted in completely different ways. Such differences are formed both from the subjectivity of the perception of these data, and from the degree of study of the material. As a result, there is a field for discrepancies and discussion.Conclusion. In order to obtain a qualitative analysis and interpretation of phenomena and processes, serious knowledge is needed, backed up by a substantial study of the subject area – only in this case statistical data can become a “mirror” reflecting the realities.